Penerapan Terapi Ballon Blowing Terhadap Saturasi Oksigen pada Pasien PPOK di Bangsal Flamboyan 7 RSUD Dr.Moewardi Surakarta - Tika Alvio Nita; Eska Dwi Prajayanti; Isti Wulandari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Chronic Obstructive Pulmonary Disease (COPD), a condition in which air flow to the lungs is limited, causing difficulty in breathing. Chronic Obstructive Pulmonary Disease (COPD) causes a decrease in oxygen levels in the blood (SpO2<85%) because oxygen flow to the lungs is reduced due to obstruction in the airways or because lung function decreases in the process of exchanging oxygen and carbon dioxide. to determine the effect of balloon blowing therapy on oxygen saturation in COPD patients in Flamboyan 7 Dr. Moewardi Surakarta ward. Descriptive application,, research sample of 2 respondents, research instrument using observation sheet and oximeter, application using balloon blowing therapy. After carrying out balloon blowing therapy times in 3 days, the respondent experienced an increase in oxygen saturation values ​​with results for Mr.S 98% and Mr.K 98%. the application of balloon blowing therapy can increase oxygen saturation in Chronic Obstructive Pulmonary (COPD) patients in Flamboyan 7 Dr. Moewardi Surakarta.